The Effectiveness of “Tell Me What is it” Android Application to Enlarge Elementary Students’ Vocabularies about Anatomy of Human Body - Meladina Meladina; Fhajri Arye Gemilang; Allans Prima Aulia (STAI Hubbulwathan Duri, 2023)
In an education context, smartphones can be used to access the application that useful for learning material about vocabulary, especially for elementary students. This research aimed to see the effectiveness of “Tell Me What is it” android application in enlarging elementary students’ vocabularies about the anatomy of the human body. Using quasi-experiment, the students in 5A and 5B in a private Islamic elementary school Bukittinggi were chosen as the research subject. The android application was applied in 5A as the experiment class, and the conventional method was used in 5B as the control class. The data were collected through tests and questionnaires and analyzed by T-dependent and independent test Sample T-test. The result of this result found that “Tell Me What is it” android application was more effective in enlarging the students’ vocabularies related to the anatomy of the human body than the conventional method. Moreover, most of the students liked the application because it was easy to use, and they felt happy when learning English with application and wanted to learn English more.